(untitled) (World Economics and Finance Bulletin, 2022)
One of the most crucial strategies used by companies to address various issues in the productive sectors is the investment in joint ventures. Companies are eager to benefit from the enhanced production of joint ventures, economic development, and access to cutting-edge technology in order to strengthen their market competitiveness. Due to this, the South Gas Company decided to collaborate in joint ventures with investors from the foreign private sector and invest in the Basra Gas Company. The purpose of the study is to apply International Accounting Standard 28 to the Iraqi South Gas Company. The research also adopted the scientific method for its research sample and financial data for the years 2012 and 2013 for both the South Gas Company and the Basra Gas Company. The results of the research played a drastic part in understanding the concept of joint ventures thoroughly, in addition to the fact that this type of investment is distinctive in comparison to other investments in the field of oil and gas in Iraq. It also contributes to supporting and better understanding of investors and executives about the nature of the standard and the relationship between the investing company and the investee company that Standard No. 28 shows but the consolidated accounting system lacks. At the time Iraq recognized applying the international standards, the research presents a practical guide for those applying the standard in the research sample company or other companies interested in applying early international standards and standard 28 as well. On the other hand, the research plays a crucial role in supporting the accounting literature related to investment in joint ventures. Additionally, it uses a novel method of measurement and disclosure and a global and local comparison of the results pertaining to the business activity of the study sample company.